(untitled) (Tzintzun, Revista de Estudios Históricos, 2020)
This paper proposes an approach to the various repercussions that it had among Spanish immigrants based in the city of Buenos Aires in the early 1930s, the beginning of the republican experience in Spain and the transformation of the colors of the Spanish flag as a national symbol. The disparity of opinions expressed towards these events was an indication of the deep ideological polarization that, years later, characterized the Spanish community in Argentina as part of the development of the Civil War in their homeland.